Study of the reaction e+e- → [psi] (2S)π+π- via initial-state radiation at BABAR - Lees, Jean-Pierre; Adametz, Aleksandra; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2014)
We study the process e+e−→ψ(2S)π+π− with initial-state-radiation events produced at the PEP-II asymmetric-energy collider. The data were recorded with the BABAR detector at center-of-mass energies at and near the Υ(nS) (n=2,3,4) resonances and correspond to an integrated luminosity of 520 fb−1. We investigate the ψ(2S)π+π− mass distribution from 3.95 to 5.95 GeV/c2, and measure the center-of-mass energy dependence of the associated e+e−→ψ(2S)π+π− cross section. The mass distribution exhibits evidence of two resonant structures. A fit to the ψ(2S)π+π− mass distribution corresponding to the decay mode ψ(2S)→J/ψπ+π− yields a mass value of 4340±16 (stat) ±9 (syst) MeV/c2 and a width of 94±32 (stat) ±13 (syst) MeV for the first resonance, and for the second a mass value of 4669±21 (stat) ±3 (syst) MeV/c2 and a width of 104±48 (stat) ±10 (syst) MeV. In addition, we show the π+π− mass distributions for these resonant regions.
Im Titel ist "psi" als griechischer Buchstabe dargestellt
Im Titel sind "+" und "-" hochgestellt
Gesehen am 11.08.2020